History of Mitigating Rolling Contact Fatigue and Corrugation of Railway Rails in Japan - Review - Makoto Ishida (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
Rail is the one of the most important materials to support and guide railway vehicles safely and smoothly. Since rail suffers from variousinteracting forces and environmental atmosphere, wear and fatigue pose large problems with wheel and rail. Hence, wear and fatigue ofwheel and rail have been studied so far to keep running safety and some level of riding comfort of vehicle taking into account trackmaintenance cost in the world. In this review, the history of theory and practice of rail maintenance in Japanese railways is describedfocusing on rolling contact fatigue (RCF) corrugation of rails caused by dynamic rolling friction at wheel/rail interface. In particular, “squat”mainly callled in UK or “rail surface shelling” called in Japan which is one of typical fatigue phenomenon for steel wheel-on-rail system andrail corrugations caused by dynamic lateral friction and vertical loading at sharp curves and/or long wavelength of rail corrugation causedby longitudinal roll-slip or stick-slip excited by the resonance of unsprung mass of bogie vertical vibration supported by track stiffness. Inaddition, the practice of countermeasure for RCF defect of squat, preventive grinding, and countermeasure for top of low rail corrugation,top of low rail lubrication “Friction Moderating System” are described. Also, the possibility of preventing long wavelength of rail corrugationformed in tangential track in undersea tunnel (salty water) enviornment is described.